Factorise:

Question:

Factorise:
(ax + by)2 + (bx − ay)2

Solution:

We have:

$(a x+b y)^{2}+(b x-a y)^{2}=\left(a^{2} x^{2}+b^{2} y^{2}+2 a x b y\right)+\left(b^{2} x^{2}+a^{2} y^{2}-2 b x a y\right)$

$=a^{2} x^{2}+a^{2} y^{2}+b^{2} y^{2}+b^{2} x^{2}+2 a x b y-2 b x a y$

$=a^{2}\left(x^{2}+y^{2}\right)+b^{2} x^{2}+b^{2} y^{2}+2 a x b y-2 a x b y$

$=a^{2}\left(x^{2}+y^{2}\right)+b^{2}\left(x^{2}+y^{2}\right)$

$=\left(x^{2}+y^{2}\right)\left(a^{2}+b^{2}\right)$

$\therefore(a x+b y)^{2}+(b x-a y)^{2}=\left(x^{2}+y^{2}\right)\left(a^{2}+b^{2}\right)$

Leave a comment

Close
faculty

Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now